2013
DOI: 10.4067/s0718-95162013005000078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar amendment on soil aggregates and hydraulic properties

Abstract: The aim of this study was to investigate the effects of biochar amendment on soil aggregate formation and stability, and soil hydraulic properties. Biochar produced from dairy manure was added to two different soils (a silty clay and a sandy loam soil) at a ratio of 2% (w/w in dry weight basis). Incubation experiments were conducted within a 90-d period with the soils (the controls) and the soil/biochar mixtures. Compared with the controls, biochar addition significantly enhanced the formation of macroaggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
111
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 30 publications
15
111
1
2
Order By: Relevance
“…) may be responsible for changes in aggregate stability within this soil type. Ouyang et al, (2013) discovered that soil macroaggregate formation increased in the early stages of a 90-d biochar incubation study, peaked in the middle and then at the later stage decreased, with little effect on microaggregation; they proposed that biochar served as a habitat for microbial growth enhancing macroaggregation, which is similar to the effect of OS biochar in this study. As a consequence of the high C:N ratio of biochar, this probably created conditions favourable to fungi (Bossuyt et al, 2001) which they suggested played a more important role in aggregate formation than bacteria (De Gryze et al, 2005).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…) may be responsible for changes in aggregate stability within this soil type. Ouyang et al, (2013) discovered that soil macroaggregate formation increased in the early stages of a 90-d biochar incubation study, peaked in the middle and then at the later stage decreased, with little effect on microaggregation; they proposed that biochar served as a habitat for microbial growth enhancing macroaggregation, which is similar to the effect of OS biochar in this study. As a consequence of the high C:N ratio of biochar, this probably created conditions favourable to fungi (Bossuyt et al, 2001) which they suggested played a more important role in aggregate formation than bacteria (De Gryze et al, 2005).…”
supporting
confidence: 68%
“…Aggregate stability is a measure of a soils structural resilience and its potential to maintain long-term crop productivity by encouraging root penetration, maintaining soil temperature and gas diffusion, improving water transport and enhancing seedling emergence. Ouyang et al, (2013) observed enhanced macroaggregate formation in a sandy loam soil amended with biochar produced from dairy manure. It was suggested that the relatively higher C/N ratio of the biochar favoured fungal growth, enhancing aggregate stability (Bossuyt et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Biochar additions to soils have had mixed results with regard to modifying soil hydraulic conductivity (K sat ) or water infiltration rates. Uzoma et al [52] and Ouyang et al [53] reported improvements in K sat after biochar additions to a silt and sandy loam-textured soil, respectively. In contrast, both Laird et al [47] and Major et al [55] reported no significant change in K sat for biochar applied to loam-and clay-textured soils, respectively.…”
Section: Biochar Influence On Soil Water Hydraulicsmentioning
confidence: 99%
“…Almost 100 years later, Tryon [45] was the first to demonstrate that soil texture was a critical factor controlling the impact of biochar on hydraulic properties. More recently, considerable attention has been given to using biochar to modify soil water hydraulics including water holding capacity and available water content [46][47][48][49][50], as well as soil hydraulic conductivity [51][52][53][54]. Laird et al [47] reported that the addition of 1 to 2 % hardwood biochar to a Midwestern USA Mollisol increased gravity drained water retention by 15 % relative to the untreated control but did not affect soil moisture content measured at soil water potentials of 33 or 1500 kPa (field capacity and wilting point, respectively) [41].…”
Section: Biochar Influence On Soil Water Hydraulicsmentioning
confidence: 99%
“…Some studies (Rondon et al, 2007;Van Zwieten et al, 2008) attributed the positive plant response to the effects of biochar on nutrients availability as well as to its capacity to increase or maintain the pH of soil, through liming. Changes in soil porosity and size aggregate distribution following biochar applications promote soil structure modifications, leading also to ameliorations of many other chemical-physical properties such as electrical conductivity (EC), CEC, pH, and water holding capacity (De Pasquale et al, 2012;Ouyang et al, 2013) that have a fundamental role in the standardization of substrate for greenhouse crops. Up to now several researches on biochar agricultural use have been focused on its application on soil, few studies were conducted in containers (Altland & Locke, 2013;Vaughn et al, 2013;Street et al, 2014;Zaccheo et al, 2014), even less regarded its utilization as growing substrate for ornamental potted plants (Tian et al, 2012;Zhang et al, 2014).…”
Section: Greenhouse Facilities and Plant Materialsmentioning
confidence: 99%